2017
DOI: 10.14423/smj.0000000000000609
|View full text |Cite
|
Sign up to set email alerts
|

Missed Opportunities for Preventing Perinatal Transmission of Human Immunodeficiency Virus, Florida, 2007–2014

Abstract: Objectives Despite declining numbers of perinatally exposed infants, an increase in perinatal human immunodeficiency virus (HIV) infections from 2011 to 2013 prompted this study to identify missed perinatal HIV prevention opportunities. Methods Deidentified records of children born from 2007 through 2014, exposed to HIV perinatally, and reported to the Florida Department of Health were obtained. Crude relative risks (RRs) and 95% confidence intervals (CIs) for factors associated with perinatal transmission, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 21 publications
2
18
0
Order By: Relevance
“…The importance of substance abuse as a predictor of late diagnosis, suboptimal antiretroviral therapy and vertical HIV transmission was also shown by several studies from the United States and Europe. 3,7,9,[14][15][16] The observed lower uptake of antenatal combination antiretroviral therapy in the adjusted analysis for Ontario and Quebec compared to British Columbia/Yukon Territory may reflect, in part, the low uptake of such therapy among women who injected drugs in Ontario and Quebec. In this regard, it is noteworthy that the uptake of antenatal combination antiretroviral therapy was relatively uniform across maternal risk categories for all provinces except Ontario and Quebec.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The importance of substance abuse as a predictor of late diagnosis, suboptimal antiretroviral therapy and vertical HIV transmission was also shown by several studies from the United States and Europe. 3,7,9,[14][15][16] The observed lower uptake of antenatal combination antiretroviral therapy in the adjusted analysis for Ontario and Quebec compared to British Columbia/Yukon Territory may reflect, in part, the low uptake of such therapy among women who injected drugs in Ontario and Quebec. In this regard, it is noteworthy that the uptake of antenatal combination antiretroviral therapy was relatively uniform across maternal risk categories for all provinces except Ontario and Quebec.…”
Section: Discussionmentioning
confidence: 98%
“…of antiretroviral treatment during pregnancy, labour and delivery, preterm delivery and incomplete avoidance of breast-feeding. [7][8][9][10][11] The objectives of the present study were to determine the adequacy, and changes over time in adequacy, of uptake of antenatal and intrapartum maternal and postpartum neonatal antiretroviral therapy for the prevention of vertical HIV transmission, and to determine the vertical transmission rate over time and according to adequacy of antenatal antiretroviral therapy during the combination antiretroviral therapy era (1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016) in Canada. We further sought to evaluate recent trends by investigating predictors of inadequate uptake of antenatal antiretroviral therapy for the period 2011-2016.…”
mentioning
confidence: 99%
“…A recent series of systematic reviews identified individual and contextual factors and health system barriers affecting ART initiation, adherence, and retention in HIV infected pregnant women [ 3 , 9 , 11 14 ]. Hodgson et al identified lower age, lower education level, HIV denial, concern ART will harm the child, misplacing/forgetting medication, use of drugs or alcohol, transportation problems, and negative attitudes of health workers as barriers to ART adherence.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, MTCT was linked to inadequate (or absent) prenatal care, and late booking of prenatal care was correlated with being foreign‐born . However, in our study, about 40% of women were Italian, highlighting that prenatal care and serological screening need to be optimized universally.…”
Section: Discussionmentioning
confidence: 51%